Preliminary selection of Lolium perenne L. natural populations for pasture improvement purpose in rainfed Mediterranean conditions - Sanna F.; Saba P.; Sassu M.; Franca A. (New approaches for grassland research in a context of climate and socio-economic changes, 2012)
Previous researchs have established how Lolium perenne L. genetic conservation, evaluation and development have priority for Mediterranean permanent pasture sustainability, and how new persistent and drought tolerant varieties could contribute to mixtures of annual and perennial legumes for pasture improvement purpose. Nevertheless, scarce is the availability of perennial ryegrass cultivars responding to semi-arid climates adaptation criteria; their persistence being reduced by incidences of summer droughts. The attempt to extend this availability has been started through a collection of germplasm and consequent field evaluation of natural populations, originating from different pedo-climatic sites of Corsica and Sardinia islands in the Mediterranean Sea, in terms of productive parameters, habit, phenology and persistence. The field evaluation trial was carried out at the Ottava experimental station of the Sassari University (570 mm average annual rainfall, North Sardinia, Italy). Starting from initial 30 natural populations, 11 preliminarily selected accessions were compared over three years, under rainfed conditions, following the UPOV rules for the identification of new cultivars, with the purpose to estimate the potential inclusion of most interesting accessions in programs that lead to varietal certification.
14. Meeting of the FAO-CIHEAM Subnetwork on Mediterranean Forages and Fodder Crops, 2012/10/03-06, Samsun (Turkey)